The Effect of Job Satisfaction and Employee Loyalty on Employee Performance - Heru Kuncorowati; Heru Noor Rokhmawati; Lalu Supardin (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
This study aims to examine the effect of job satisfaction and employee loyalty on employee performance in Ros-In Hotel at Yogyakarta. Respondents in this study were employees of Ros-In Hotel. The number of respondents in this study were 50 respondents. Sampling was done by purposive sampling technique. This study uses multiple linear regression analysis technique with SPSS as an analytical tool. Based on the results of data testing, it shows that: 1) Job satisfaction partially has a significant effect on employee performance in Ros-In Hotel at Yogyakarta. 2) Employee loyalty partially has a significant effect on employee performance in Ros-In Hotel at Yogyakarta. 3) Job satisfaction and employee loyalty simultaneously have a significant effect on employee performance in Ros-In Hotel at Yogyakarta